3D geometrically structured PANI/CNT-decorated polydimethylsiloxane active pressure and temperature dual-parameter sensors for man–machine interaction applications. Issue 30 (27th July 2020) - Wang, Yalong; Mao, Hongye; Wang, Yao; Zhu, Pengcheng; Liu, Chenghao; Deng, Yuan
Abstract : A dual-parameter sensor with high sensitivity, broad response range, fast response and long-term stability in practical sensing application scenarios has been demonstrated. Abstract : Wearable sensors integrating multiple functionalities have emerged with great potentials in artificial smart systems for perceiving external stimuli such as strain, stress and temperature simultaneously with high sensitivity. Yet, it is a great challenge to accomplish multiple functions in a single device without signal interference or compromising the sensitivity of each function. In this work, we developed a pressure/temperature dual-parameter sensor with 3D geometric architecture employing thermoelectric polyaniline/carbon nanotube composite film-decorated porous polydimethylsiloxane. The sensor is capable of detecting static/dynamic pressure signals with a high sensitivity of 91.8% kPa −1 up to 130 kPa, fast response time, and long durability. Meanwhile, the sensor responds to static/dynamic temperature variation with a sensitivity of 17.1 μV K −1 together with long-term stability. Finite element analyses revealed the local pressure/current and temperature/electric potential distribution to further explain the sensing performances. A series of responses to external stimuli in practical scenarios prove that the dual-parameter sensor exhibits sensitive movement monitoring and surrounding temperature-perceiving capabilities simultaneously without signal interference. Moreover, the application of the developed sensor in a practical scenario shows accurate multichannel signal communication with a computer in real time. Our study thus provides a promising strategy for multifunctional sensors applied in human–machine interactions.